Perceived barriers to bicycling in an urban U.S. environment. (September 2017) - Fowler, Stephanie L.; Berrigan, David; Pollack, Keshia M.
Abstract: Prior research has identified several barriers influencing decisions to bicycle, including infrastructure, safety, and environmental factors. There is scant research exploring how sex and ridership status correlate with perceived barriers, which is a known barrier to being physically active. A total of 1334 Baltimore City residents aged 18 to 75 participated in an online survey (February-March 2014) assessing the major barriers to bicycling in the city. Differences by sex and ridership status were examined independently and interactively. Most respondents were women (60%) and not regular riders (66%). Safety due to traffic was the biggest barrier for non-riding women (77%) and non-riding men (54%). Weather was the biggest barrier for riding women (55%) and riding men (51%), followed by safety due to drivers (45% and 33%, respectively). Sex and ridership differences were also found for barriers regarding preference and logistics of transport. For example, riders had lower odds than non-riders of rating biking as less comfortable than driving as a major barrier, OR=0.39, p <0.01. Furthermore, women had greater odds than men of rating it is difficult to carry things on a bike as a major barrier, OR=1.65, p <0.01. Interactions between sex and ridership status revealed that riding women had lower odds than riding men of rating a) needing others to travel, OR=0.32 and b) hygiene, OR=0.41, as major barriers, p 's<0.05. We discuss these findings in the broader context of the literature, and offer strategies for addressing specific barriers to bicycling.